2020
DOI: 10.1080/2162402x.2020.1832348
|View full text |Cite
|
Sign up to set email alerts
|

Baseline plasma levels of soluble PD-1, PD-L1, and BTN3A1 predict response to nivolumab treatment in patients with metastatic renal cell carcinoma: a step toward a biomarker for therapeutic decisions

Abstract: Despite a proportion of renal cancer patients can experiment marked and durable responses to immunecheckpoint inhibitors, the treatment efficacy is widely variable and identifying the patient who will benefit from immunotherapy remains an issue. We performed a prospective study to investigate if soluble forms of the immune-checkpoints PD-1 (sPD-1), PD-L1 (sPD-L1), pan-BTN3As, BTN3A1, and BTN2A1, could be candidate to predict the response to immune-checkpoint blockade therapy. We evaluated the plasma levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 43 publications
0
79
0
Order By: Relevance
“…It has also been observed that miR-200 expression negatively correlates with PD-L1 expression, suggesting the potentiality of miRNA expression as a predictive biomarker for immunotherapy response [ 44 ]. Previous studies showed that baseline levels of soluble PD-1 and PD-L1 were associated with a longer PFS to nivolumab treatment in a cohort of metastatic ccRCC patients, and high sPD-1 were also associated with best overall response by RECIST and objective response of >20% [ 45 , 46 , 47 ]. In our patient cohort, the inverse correlation between miR-22 and miR-24 levels and plasma PD-1 levels in long-responder patients suggests that a miRNA network could inhibit the immune checkpoint expression, mainly via the miR-20 family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that miR-200 expression negatively correlates with PD-L1 expression, suggesting the potentiality of miRNA expression as a predictive biomarker for immunotherapy response [ 44 ]. Previous studies showed that baseline levels of soluble PD-1 and PD-L1 were associated with a longer PFS to nivolumab treatment in a cohort of metastatic ccRCC patients, and high sPD-1 were also associated with best overall response by RECIST and objective response of >20% [ 45 , 46 , 47 ]. In our patient cohort, the inverse correlation between miR-22 and miR-24 levels and plasma PD-1 levels in long-responder patients suggests that a miRNA network could inhibit the immune checkpoint expression, mainly via the miR-20 family.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma sPD-1 and sPD-L1 levels have been previously measured using specific homemade ELISA assays not yet commercially available, designed according to the investigator specifications, as previously described [ 47 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…[50] in the following way: progression disease (PD), stable disease (SD), partial response (PR), complete response (CR). The peripheral blood specimens from untreated GIST patients (baseline) were processed for plasma isolation and subsequently stored as previously described [16,22].…”
Section: Study Populationmentioning
confidence: 99%
“…In the previous NIVOREN GETUG-AFU 26 study, it was reported that tissue PD-1 and AXL expression by immunohistochemistry were associated with PFS and confirmed that PBRM-1 loss was a strong prognostic factor (10). Incorvaia et al explored the prognostic value of soluble forms of PD-1, PD-L1, global BTN3, BTN3A1 and BTN2A1 in a prospective cohort of metastatic renal cell carcinoma patients (11). They identified sPD-1, sPD-L1 and sBTN3A1 as potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%